Scientific Contribution of AE-IC’s Conferences (2008-2014): Historic Overview and the Current State of Communication Research - Rodríguez Gómez, Eduardo Fco. (Historia y Comunicación Social, 2016)
This paper presents a study of the Spanish scientific contribution presented at the Asociación Española de Investigación de la Comunicación conferences in order to understand its development and current state. To achieve this, twenty-two variables have been recorded for 715 papers, including: author, gender, institutional affiliation, nationality, type of communication, methodology, descriptive typology, contents replication and author’s aims. Among other findings, our results show a female majority in the academic contribution, but not among senior academic positions; a preference for business studies, but not for social or working conditions studies; a trend towards a greater participation by doctoral candidates; and a high concentration of scientific production regarding territorial and thematic features.
Keywords: AEIC; communication research; conferences; scientific production; papers